Training Surgery Residents to be Leaders: Construction of a Resident Leadership Curriculum. Issue 3 (March 2022) - Stein, Matthew K.; Kelly, John D.; Useem, Michael; Donegan, Derek J.; Levin, L. Scott
Abstract : Summary: Historically, the traditional pathways into plastic surgery required board eligibility in a surgical specialty such as general surgery, orthopedics, urology, neurosurgery, otolaryngology, or ophthalmology. This requirement resulted in plastic surgery residents who had served as chief residents before plastic surgery training. Their maturity emotionally and surgically allowed them to immediately concentrate on the new language and principles of plastic surgery. They had led others and were capable of leading themselves in a new surgical discipline. Today, medical students typically match into surgical specialties directly out of medical school and need to spend their time learning basic surgical skills and patient care because of the contracted time afforded to them. Formal leadership training has historically been limited in surgical training. The authors set out to delineate the creation, implementation, and perceptions of a leadership program within a surgical residency and provide guideposts for the development of engaged, conscious, and dedicated leaders within the residencies they lead.